PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI DINAS ENERGI DAN SUMBER DAYA MINERAL KABUPATEN MAMUJU UTARA - Alam, Nur (Katalogis, 2016)
The aim of this study; (1) untuk mengetahui and analyze the influence of intrinsic and extrinsic motivation simultaneously on the performance of employees at the Department of Energy and Mineral Resources of North Mamuju regency; (2) to assess and analyze the effect of intrinsic motivation partially on the performance of employees at the Department of Energy and Mineral Resources of North Mamuju regency; (3) to mengetahui menganalisis pengaruh extrinsic motivation partially on the performance of employees at the Department of Energy and Mineral Resources of North Mamuju regency. This type of research inikuantitatif. Population research staff at the Department of Energy and Mineral Resources of North Mamuju regency totaling 40 people with census sampling techniques so that the entire population sampled. Data collection techniques including observation, questionnaires, and documentation, and data analysis technique multiple linear regression. The results showed; (1) There is the influence of intrinsic and extrinsic motivation simultaneously on the performance of employees at the Department of Energy and Mineral Resources of North Mamuju regency with the influence of 62.9% and the level of the strong relationship between variables; (2) There is the influence of intrinsic motivation partially on the performance of employees at the Department of Energy and Mineral Resources of North Mamuju regency. Intrinsic motivation in this research are influenced by the recognition as recognition of the work ability, whereas the intrinsic motivation of employees who have indicated is a matter of individual responsibility as the completion of the work not on time; (3) There is the influence of motivation eksrinsik partially on the performance of employees at the Department of Energy and Mineral Resources of North Mamuju regency. Extrinsic motivation in this research are influenced by incentives, while extrinsic motivation is the employee who has not obtained adequate working facilities used.